2011
DOI: 10.1088/0031-9155/56/14/016
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory motion blur identification and reduction in ungated thoracic PET imaging

Abstract: Respiratory motion results in significant motion blur in thoracic positron emission tomography (PET) imaging. Existing approaches to correct the blurring artifact involve acquiring the images in gated mode and using complicated reconstruction algorithms. In this paper, we propose a post-reconstruction framework to estimate respiratory motion and reduce the motion blur of PET images acquired in ungated mode. Our method includes two steps: one is to use minmax directional derivative analysis and local auto-corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…It is found that for small iterations (e.g. 2), MCIR outperforms in the aspect of bias and Co V and has similar noise distribution to RTA. However, for large iterations RTA has improved CoY than MCIR.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…It is found that for small iterations (e.g. 2), MCIR outperforms in the aspect of bias and Co V and has similar noise distribution to RTA. However, for large iterations RTA has improved CoY than MCIR.…”
Section: Discussionmentioning
confidence: 89%
“…F OLLOWING the continuous improvements in PET spatial resolution [1], respiratory motion is becoming a limiting factor for PET performance [2]- [4]. Respiratory motion correction is a difficult problem due to the poor statistical quality of PET data and many approaches have been previously investigated [5].…”
Section: Introductionmentioning
confidence: 99%
“…Patient respiratory motion is a source of quantitation errors in positron emission tomography (PET), due to the degradation of the image resolution and potential misalignment with the attenuation map ( μ ‐map) used for attenuation correction (AC), which is derived from computed tomography (CT) or magnetic resonance imaging (MRI) . Both phenomena can compromise accurate detection and quantitation of lesions in the reconstructed PET .…”
Section: Introductionmentioning
confidence: 99%
“…Respiratory organ motion degrades the accuracy of diagnostic imaging and image guided interventional procedures [1] [2] [3]. Respiratory motion modelling attempts to alleviate the detriment in the aforementioned areas [4] [5].…”
Section: Introductionmentioning
confidence: 99%